2015
DOI: 10.3126/eco.v21i0.11900
|View full text |Cite
|
Sign up to set email alerts
|

Some Biological Characteristics of the Daysciaena albida (Cuvier 1830), on Largest Brackish Water Lagoon of India

Abstract: An attempt to study length-weight relationship (LWR), condition factor and reproductive aspects of Daysciaena albida was done in Chilika lagoon over one year. The fish specimens for the biological study were collected from landing centers of central and northern sector during pre-monsoon, monsoon and post-monsoon seasons. The LWR from total length and body weight were computed both by sex and seasons. The equations found from the relationships were y=0.010x 2.992 for male, y=0.010x 2.998 for female and y=0.010… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…De et al (2013) [5] in West Bengal showed different result and mentioned that copepods were the major items in the guts of hilsa from 10 g to 30 g, followed by diatoms which also supported the present study result. The percentage frequency of the existence of sand particles (5-15%) was discovered in the present study result which was also reported by Karna et al (2014) [11] .…”
Section: Frequency Of Occurrence (Foc %)supporting
confidence: 89%
See 2 more Smart Citations
“…De et al (2013) [5] in West Bengal showed different result and mentioned that copepods were the major items in the guts of hilsa from 10 g to 30 g, followed by diatoms which also supported the present study result. The percentage frequency of the existence of sand particles (5-15%) was discovered in the present study result which was also reported by Karna et al (2014) [11] .…”
Section: Frequency Of Occurrence (Foc %)supporting
confidence: 89%
“…Plankton were identified to the genus level following the determination keys of Yamaji's (1984) [19] and Sahu et al (2013) [16] . The frequency of occurrence method (Hynes, 1950; Hyslop, 1980) [6] [10] , volumetric analysis method (Hynes, 1950) [6] and index of relative importance (Pinkas, 1971) [12] were used to estimate the gut contents quantitatively.…”
Section: Gut Content Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The frequencies (%F) of sand particles we observed to be decreased with increased fish sizes, suggesting feeding by young hilsa in the nearshore, in epibenthic habitats. The presence of sand particles in hilsa guts, however, was also reported by [31]. Hora and Nair (1940) [32] reported sand grains in hilsa guts from the West Bengal waters, India, and they suggested that hilsa fish feed at the bottom, but no other studies considered the presence of sand in hilsa guts as indicators of feeding habitat in Bangladeshi riverine areas.…”
Section: Frequency Of Occurrence (%F)mentioning
confidence: 88%